Examining Student Conception of Reaction Rate Through Three-Tier Multi-Representation Assessments - Magfirah, Magfirah; Alimuddin, Chatifah; Santoso, Tri; Afadil, Afadil; S. Ahmar, Dewi; Rahmawati, Sitti (Jurnal Akademika Kimia, 2023)
This study aims to analyze students' conceptions of reaction rate topics using the three-tier multi-representation test. Based on the characteristics of reaction rates concepts that involve the understanding of multiple representations, it is essential to analyze student conceptions that include multiple representations, namely macroscopic, microscopic, and symbolic. A three-tier diagnostic test can be done to assess students' conceptions, with the questions given in the first tier presented with macroscopic, microscopic, or symbolic representations according to the characteristics of the concept in question. This research uses a descriptive quantitative method conducted at Madrasah Aliyah Negeri 2 in Palu City, Central Sulawesi. The subjects of this study were 50 students consisting of 28 female students and 22 male students. It was determined by random sampling technique. Instrumentation used a three-tier representation test with 15 multiple-choice questions. Validation of instruments showed that the questions were feasible and fell into the high category. The findings reveal that only 29 % of students know the concept, categorized as low. Additionally, 40 % of students were identified as having misconceptions, placing them within the medium category, while 31 % of students exhibited not knowing the concept, also classified in the medium category. Symbolic representation emerged as the most challenging representation for students, with 35 % failing to comprehend it, categorized as medium. Furthermore, among students with misconceptions, symbolic and macroscopic representations were the most problematic, collectively accounting for 34 %, also classified as medium. These results underscore the need for targeted instructional strategies to address specific areas of difficulty and improve overall conceptual understanding.